Dose de exposição radiométrica de granitos do estado de Rondônia, Brasil - Bonotto, Daniel Marcos [UNESP] (2009)
This work evaluated the activity concentration of the radioelements K, eU and eTh in samples of granites from Rondônia State, Brazil. The statistical analysis of the data indicated that they fit lognormal distributions. The modal values correspond to about 11% for K, 29 ppm for eU and 85 ppm for eTh. Directsignificant correlations were found among the concentrations of the three radioelements, i.e. r = 0.71 (between K and eU), r = 0.72 (between K and eTh), andr = 0.72 (between eU and eTh), suggesting congruency of their accumulation in minerals occurring in the rocks analyzed. The activity concentration data allowed estimate the absorbed dose rate in air at 1 m above the ground, which also fits a lognormal distribution characterized by a mode of 2.7 mSv/y that is slightly higher than the average worldwide exposure of 2.4 mSv/y. The results obtained also allowed evaluate if the granites analyzed are radiometrically suitable as building and ornamental materials. © 2009 Sociedade Brasileira de Geofísica.